Неизотермическая кинетика в термическом анализе полимеров. 2. Изоконверсионный анализ - Крамаренко, Виктор Юрьевич (НТУ "ХПИ", 2015)
Большинство процессов образования и деструкции полимеров не могут быть представлены кинетическими уравнениями формально простых реакций. Как следствие, для решения кинетических задач широко используется изоконверсионный подход, предполагающий, что кажущаяся энергия активации сложного процесса может изменяться в зависимости от его степени завершенности. В предлагаемой работе представлен алгоритм обработки экспериментальных данных неизотермических измерений и определения кинетических параметров на основании такого подхода. Апробация осуществлена на примере сравнения результатов простой реакции второго порядка и автокаталитической реакции отверждения эпоксиаминных систем.

The kinetic studies of thermally induced reactions of polymers, such as cure of oligomers or thermal destruction, are traditionally performed by thermal analysis in non-isothermal regime. Investigations of such complex processes do not allow a change of a measured heat (DSC) or mass loss (thermogravimetry) to be separated into contributions from single reactions. The isoconversional method or free-model approach is widely used for kinetic description of such complex processes by assumption of possible dependency of apparent activation energy from the extent of reaction. An algorithm of experimental data treatment for non-isothermal measurements has been presented in this study. Two types of reactions, namely of two-order and autocatalytic reactions of epoxyamine cure have been considered for comparison of results of isoconversional analysis. In spite of similarity of extent reaction dependencies from temperature in non-isothermal regime, the modeling curves in isothermal conditions are demonstrated clear distinctions between two reaction types.
Non-isothermal kinetics in the thermal analysis of polymers. 2. Isoconversional analysis
Keywords: кинетика формальная; реакция автокаталитическая; система эпоксиаминная; formal kinetics; complex reactions; autocatalylic kinetics